Public equity markets and innovation - Shai Bernstein (Asian Development Bank Institute (ADBI), 2017)
This paper reviews the literature on the role of public equity markets in the innovation ecosystem. The review highlights the importance of public equity markets in funding the research and development activities of young and high growth firms. It also illustrates the dependence of venture capital firms, which provide an important source of capital to early-stage start-ups, on the performance of public equity markets and the initial public offering market in particular. Finally, the paper discusses the potential shortcomings of public equity markets that may hinder innovation, and highlights various mechanisms that may alleviate such concerns.
Keywords: G21; G24; L26; M13; O31; O32; 330; public equity markets; finance; innovation; entrepreneurship; agency problems; venture capital